2009
DOI: 10.1007/s12178-008-9041-4
|View full text |Cite
|
Sign up to set email alerts
|

Cervical epidural steroid injections in the management of cervical radiculitis: interlaminar versus transforaminal. A review

Abstract: There has been recent concern regarding the safety of cervical epidural steroid injections. The decision to proceed with treatment requires balancing the risk and benefits. This article is an in depth review of the efficacy, complications, and technique of both interlaminar and transforaminal cervical epidural steroid injections in the management of cervical radiculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 83 publications
1
61
0
3
Order By: Relevance
“…Her iki yaklaşımın da fatal seyreden komplikasyonları olabilmektedir. [13,[19][20][21] Literatürde verilen SESİ'den memnuniyet oranları %40-95 arasında değişmektedir. [4,22] Bu oranlar, ça-lışmamız sonuçları ile uyumlu görülmektedir.…”
Section: Sayı Dağılımunclassified
See 2 more Smart Citations
“…Her iki yaklaşımın da fatal seyreden komplikasyonları olabilmektedir. [13,[19][20][21] Literatürde verilen SESİ'den memnuniyet oranları %40-95 arasında değişmektedir. [4,22] Bu oranlar, ça-lışmamız sonuçları ile uyumlu görülmektedir.…”
Section: Sayı Dağılımunclassified
“…[13] Servikal spinal kanalın sagital ça-pının dar olması semptomların ortaya çıkışında en büyük role sahipken, sagital çapın geniş olduğu ve MRG bulgularında disk protrüzyonu yaygın olarak tespit edildiği halde bazı hastalarda belirti olmayabilir. [2] Böyle hastalarda servikal sagital çap, semptomların ortaya çıkışında belirleyici olabilmekte, zira MRG bulguları ile disk protrüzyonu tespit edildiği halde, sagital çapın genişliği nedeniyle spinal kord üzerine bası gerçekleşmemektedir.…”
Section: Kaynaklarunclassified
See 1 more Smart Citation
“…The cause of these symptoms may lie in anatomical change. Cervical radiculitis affects approximately 83 per 100,000 of the population each year (3). Except intervertebral disc herniation it can be caused by osteoproductive changes in vertebrae, degenerative changes in joints, etc.…”
mentioning
confidence: 99%
“…1,2 Concerns have developed over the safety of this procedure, however, with reports of serious complications in the literature. [3][4][5] Some authors have suggested that the interlaminar approach for performing injections may be associated with a lower risk of catastrophic injury than the transforaminal approach, though spinal cord injury remains a possibility with either approach. [6][7][8][9] As such, many authors advocate limiting interlaminar epidural steroid injections to the C6-C7 level or below to reduce the risk of cord injury.…”
mentioning
confidence: 99%